(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The conventional asset-backed lending business is often reliant on outdated data management platforms and opaque storage platforms, presenting the industry with very daunting problems, including security breaches, the lack of verifiable ownership histories, and obscure asset disposal practices. To address this, this study came up with a safe web-based system that digitalizes the activities of loans by applying the blockchain technology. The platform is integrated with a modern online architecture, which uses a Virtual Vault Guard to implement the dual-key access protocol, as well as AES encryption and SHA-256 hashing that would guarantee that data about the assets are safely secured on-chain. Smart contracts were automated to create digital receipts that were immutable and to conduct digital bidding of defaulted loans in an atomic swap. The empirical research indicates that the ecosystem improves the general performance of management in terms of availing very structured, secure digital data storage and reliable auditing facilities. The paper concludes that the implementation of a blockchain-based system, which is associated with immutable receipts and transparent bidding, is necessary to ensure complete security, fairness, and efficiency. Based on this, the study suggests that the lending institutions should incorporate this secure ledger of assets and automated system of bidding to enhance customer confidence by providing verifiable digital receipts as well as to provide fair and transparent recovery of capital.